Molecular cloning and expression analysis of stress-inducible protein I gene of Miichthys miiuy - SUN Yue-na; XU Tian-jun; SHI Ge; WANG Ri-xin (浙江大学学报. 农业与生命科学版)
The full length of stress-inducible protein I (STI1) gene cDNA was cloned from Miichthys miiuy based on the obtained EST sequence using rapid amplification of cDNA ends polymerase chain reaction (RACE-PCR). The STI1 gene cDNA consisted of 2 194 nucleotides including 5 untranslated regions (UTR) of 31 nucleotides, 3 UTR of 634 nucleotides and open reading frame with 1 629 nucleotides encoding 542 amino acid residues. The molecular structure of STI1 consisted of five potential casein kinase II phosphorylation sites, one polyproline stretch, two nuclear localization signals and nine tetratricopeptide repeats (TPR). The amino acid sequence of the STI1 gene shared 76.5%-94.3% identity with those of previously reported other species STI1 gene including conserved eight cysteines. Phylogenetic tree analysis based on amino acid sequences of STI1 gene generated by neighbor-joining method suggested that four teleosts clustered together, and were close genetic relationship between M. miiuy and Pseudosciaena crocea. Real-time PCR showed that the STI1 gene was mainly detected in muscle and kidney.